Strategic profiles in Brazil: a study of postal agents franchisees from the typology of Miles and Snow - Lopes, Humberto Elias Garcia; Moura, Thelmo Naves; Oliveira, Caio César Gianinni (Review of Business Management, 2010)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> This paper consisted of a descriptive study in franchised postal agencies located in 110 municipalities of Minas Gerais. Its objective was to examine whether the strategic typology originally proposed by Miles and Snow (1978) and adapted by DeSarbo et al. (2005), was able to differentiate adaptation strategies of the sample. For this With this objective in mind we’ve made a survey in which data were collected through the questionnaire proposed by DeSarbo et al. (2005). These data were analyzed by descriptive statistics and cluster analysis, multivariate technique that allows the identification of similarities among the respondents. The study has investigated the differences between strategic profiles identified in the sample in relation to its strategic capabilities and their perceptions of environmental risks. The results indicated that the typology proposed by DeSarbo et al. (2005) is able to differentiate adaptation strategies of companies in a franchise network. Further test results allowed considering relevant and enriching way of investigation of strategic capabilities and environmental uncertainties of the method proposed by the authors. Key words: <!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>Strategic types. Adaptation. Cluster analysis.